2014
DOI: 10.1159/000362878
|View full text |Cite
|
Sign up to set email alerts
|

Population-Genetic Influences on Genomic Estimates of the Inbreeding Coefficient: A Global Perspective

Abstract: Background/Aims: Culturally driven marital practices provide a key instance of an interaction between social and genetic processes in shaping patterns of human genetic variation, producing, for example, increased identity by descent through consanguineous marriage. A commonly used measure to quantify identity by descent in an individual is the inbreeding coefficient, a quantity that reflects not only consanguinity, but also other aspects of kinship in the population to which the individual belongs. Here, in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 85 publications
(69 reference statements)
4
43
2
1
Order By: Relevance
“…Nevertheless, evidence from countries that have data based on different sources suggest consistency over time and sampling method. Studies comparing Bitles's data to genetic correlates of inbreeding find that both methods paint a consistent picture (Leutenegger et al, 2011, Pemberton andRosenberg, 2014).…”
Section: Appendix C -Data Sourcesmentioning
confidence: 98%
“…Nevertheless, evidence from countries that have data based on different sources suggest consistency over time and sampling method. Studies comparing Bitles's data to genetic correlates of inbreeding find that both methods paint a consistent picture (Leutenegger et al, 2011, Pemberton andRosenberg, 2014).…”
Section: Appendix C -Data Sourcesmentioning
confidence: 98%
“…33 Differences in the presumed frequency of inbreeding suggested by the F IS coefficient often reflect the influences of genetic isolation and genetic drift, including past population bottlenecks and founder effects rather than consanguineous marriage. 37 Differences in the F IS coefficient may also reflect differences in study quality, including mistaken attribution of genotype due to testing errors and selection bias. A study that analyzed data from 26 populations around the world with both F IS coefficients and estimates of consanguinity found that the latter explained a little more than one-tenth of variation in the former (r = 0.349, p = 0.040).…”
Section: Discussionmentioning
confidence: 99%
“…A study that analyzed data from 26 populations around the world with both F IS coefficients and estimates of consanguinity found that the latter explained a little more than one-tenth of variation in the former (r = 0.349, p = 0.040). 37 …”
Section: Discussionmentioning
confidence: 99%
“…by calculating the number of individuals born outside the small community as was done in Palawan. Measures of endogamy may also been done [5]. 4) The measure of particular genetic variations in high risk groups vs. control groups to confirm their common origin.…”
Section: Research Directionsmentioning
confidence: 99%
“…Endogamy is influenced by the size of the population and the level of isolation, in addition to legal, cultural and religious practices. Isolation, through its limitation of the number of potential spouses, is a major risk factor of endogamy, as shown by significant correlations between measures of genetic isolation and measures of inbreeding [5]. Endogamy has been associated with higher mortality and morbidity, including complex disorders like mental and behavioral disorders [3].…”
Section: Introductionmentioning
confidence: 99%